River Water Pollution Monitoring using Multiple Sensor System of WSNs - Evizal Abdul Kadir; Hitoshi Irie; Sri Listia Rosa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
The river is a natural phenomenon thatcommonly available in the tropical region because of rainintensity. Many peoples and community like to live along theriverside for a few decades ago. The river used by thecommunity for transportation and daily activities uses riverwater. In this research objective to design and develop a newsystem with multiple sensors system to monitor river waterpollution because most of the people use it. Wireless SensorNetworks (WSNs) used in this design and developmentbecause of advantages WSNs system, multiple sensor nodesinstalled for detection of water pollution such as watertemperature, pH, electrical conductivity (EC) and dissolvedoxygen (DO). The system designed to be able to monitorriver water pollution parameters and send the information tothe data center (backend system). Arduino microcontrollerused to process and filtering the data before sending to thebackend system, only valid and valuable information tocollect and keep in the database. Results show system be ableto detect polluted water with indicating parameters andshows in a graph. Based on analysis can be concluded thatpolluted water indicator mostly from residence waste andindustry. Furthermore, WSNs sensors will deploy in somearea then compare the results each other.